Allergic contact dermatitis of the scalp: a review of an underdiagnosed entity - Jonathan C. Hwang, BS; Colleen J. Beatty, MD; Kuzma Khobzei, MD; Viktoryia Kazlouskaya, MD, PhD (International Journal of Women's Dermatology, 2024)
Background:. It is hypothesized that scalp allergic contact dermatitis (ACD) in women is commonly mistaken for other disorders due to overlapping symptoms and unique clinical presentations. Objective:. This study reviews the potential underdiagnosis and misdiagnosis of scalp ACD and explores ways to improve diagnostic accuracy. Methods:. This study conducted an extensive literature review to identify diagnostic challenges, common misdiagnoses, and diagnostic approaches for scalp ACD, focusing on standard versus targeted patch testing techniques. Results:. Scalp ACD, often misdiagnosed as seborrheic dermatitis due to similar symptoms, has atypical presentations such as hair thinning, hair loss, and erythematous lesions affecting neighboring regions. Trichoscopy can help distinguish scalp ACD, identifying its patchy distribution of thin white scales, in contrast to the yellow scaling of seborrheic dermatitis. Standardized patch testing further contributes to diagnostic errors, with a study reporting 83% of patients who tested negative with standardized patch tests were positive when using their personal products. Individualized patch testing is more effective in identifying causative allergens and accurately diagnosing scalp ACD. Limitations:. It is a retrospective review. Conclusion:. Several factors contribute to scalp ACD’s misdiagnosis for conditions such as seborrheic dermatitis. The significant discrepancy in ACD detection rates between personalized and standardized patch tests in women emphasizes the importance of using patient-specific products in diagnostic testing. Incorporating scalp ACD more readily into one’s differential, employing individualized patch testing with trichoscopy, and accounting for neighboring symptomatic areas are all crucial elements in improving diagnostic accuracy for scalp ACD in women.